Magnetohydrodynamic Unsteady Free Convection Flow Of a Viscoelastic Fluid Along a Vertical Plate - Ibrahim, F.N. (Engineering Transactions, 1991)
The unsteady free convection flow of an incompressible electrically conducting viscoelastic fluid past an oscillating vertical plate in the presence of a transverse magnetic field has been studied. The flow phenomena have been characterized by the nondimensional numbers P (Prandtl number), G (Grashof number), m (magnetic number), ω (frecuency number) and k (viscoelastic parameter). It is found that the temperature profile may be compared with a damped harmonic wave propagating in a direction perpendicular to the plate. The dimensionless temperature as well as the thermal boundary layer δT increase with the decrease of P. The effects of P, G and m on the velocity field ur and velocity boundary layer thickness δ for the viscoelastic fluid are similar to that for a Newtonian fluid. As k increases, ur and b increase simultaneously. Opposite effects are noticed at a certain distance away from the plate. The skin friction rr at the plate is estimated for different values of P, G, m and k.